Application of International Rules Ensuring Social Rights of Families and Children in Kazakhstan - OMAROVA, Ayman Bekmuratovna; TAITORINA, Binur Adamovna; YERMEKOV, Adlet Tokhtamysovich; DOSZHANOV, Bulat; BURIBAYEV, Yermek Abiltayevich; KHAMZINA, Zhanna Amangeldinovna (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The objective of the present study is to work out the recommendations and suggestions aimed at further development of legal bases of social protection of families and children considering their international standards as a promising direction of legal science and the most important direction of social policy. The authors subsequently consider the forms of strengthening the international standards of rights of families and children; define the directions of improving fulfillment of the international obligations of Kazakhstan in provision of the social rights; reveal the problems of taking by the Republic of Kazakhstan (RK) of legislative, organizational, financial and economic measures in compliance with the constitutional procedures for the purpose of ensuring accepted social rights of family and children. The basic methods are the methods of description and analysis of the situations caused by social and economic peculiarities of Kazakhstan as well as the modern state of its sphere of social protection. As a result of the conducted research considering the provisions and the level of the international norms and standards the authors represent the conclusions and suggestions for improvement of the legal and organizational infrastructure for ensuring social rights of families and children in the RK.